CAMPURAN BERASPAL PORUS DWILAPISAN SEBAGAI LAPIS PERMUKAAN JALAN YANG RAMAH LINGKUNGAN DI PERKOTAAN - ., Hardiman (Jurnal Transportasi, 2008)
AbstractÂ The pleasurable of driving on roads with high level of safety is expected by all road users in developed and developing countries. Communities who live in big cities near to road crossings definitely do not expect noise that which could disturb their daily lives. In this paper, several research findings will be presented related to double layer porous asphalt, in laboratory as well as its application, in some developed countries. It is shown that the use of finer upper layer with less thickness could function as noise reducer. In addition, the double layer porous asphalt has the level of noise very much lower than those of other conventional asphalts. However, the porous asphalt needs maintenance to prevent its void from clogging of debris and other small materials. Another factor that could reduce its service life is the influence of over-loaded vehicles which causes the voids become smaller.Â Keywords: Double layer porous asphalt, environment, noise, voids and permeability.